Homeostatic plasticity in patients with disorders of consciousness detected by combined stimulation: a study protocol - Jingwen Wang; Jingwen Wang; Fangfang Shou; Qiuyi Yu; Xulan Lu; Yuwen Wan; Yuwen Wan; Wangshan Huang; Nantu Hu; Zhenyi Jin; Xinru Shan; Steven Laureys; et al. (Frontiers in Neurology)
BackgroundNon-invasive neuromodulation (NIN) techniques have been widely utilized in treating patients with disorders of consciousness (DoC), but their therapeutic effects have been inconsistent. Given the reliance of NIN techniques on synaptic plasticity, and the potential impairment of synaptic plasticity (particularly homeostatic plasticity) resulting from severe brain injury, it is possible that the variation in therapeutic effects is due to alterations in homeostatic plasticity in patients with DoC. Therefore, this study will use preconditioning TMS to examine the retention of homeostatic plasticity in patients with DoC.MethodsWe will enroll 30 patients with DoC and 15 healthy controls and randomize the order of their sessions. According to the priming protocol, the trial was divided into three different sessions with a 2-day break between each session. The session will involve a 10-min duration of transcranial direct current stimulation (tDCS) priming, followed by a 192-s period of transcranial magnetic stimulation (TMS) test. Transcranial stimulation will be specifically targeted toward the left primary motor cortex. Measurements of motor evoked potentials will be taken at several time points: baseline, after tDCS, and after TMS. Coma Recovery Scale-Revised will be conducted both baseline and after TMS.DiscussionStudying whether homeostatic plasticity is preserved in patients with DoC is beneficial for gaining a better understanding of their brain condition. If the homeostatic plasticity of patients with DoC is impaired, then NIN, which are based on altering synaptic plasticity in healthy individuals to achieve stimulating effects, may not be directly translatable to the therapeutic interventions for patients with DoC. Instead, the homeostatic plasticity of patients should be restored before implementing the intervention.